Hubungan Sense of Humor dengan Academic Burnout pada Fungsionaris Lembaga Kemahasiswaan di Universitas Kristen Satya Wacana - Litaay, Cindy Christine; Rahayu, Maria Nugraheni Mardi (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the relationship between sense of humor with burnout on functionaries Lembaga Kemahasiswaan in SWCU. Subjects were 296 functionaries of LK UKSW, sample selection with quota sampling. The measuring instrument used to measure academic burnout is the Maslach Burnout Inventory Student Survey (MBI-SS). Sense of humor is measured by the Multidimensional Sense of Humor Scale. Statistical data analysis using Spearman Product Moment correlation. The results of this study found that there is no significance relationship between sense of humor and academic burnout on functionaries of LK UKSW (r = 0.094 and sig = 0.107). Functionaries are expected to find appropriate coping strategies with the help of lectures and Lembaga Kemahasiswaan in the process of finding and implementing these coping strategies.